HUBUNGAN KADAR PROCALCITONIN DAN JUMLAH LEUKOSIT PAD PASIEN COVID-19 DI RSUD PASAR REBO - Desi Aryani (Yayasan Pendidikan Medika Indonesia, 2022)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). This disease attacks the respiratory system, in severe cases SARS-CoV-2 infection can cause respiratory tract infections which are characterized by a systemic inflammatory response in acute respiration that can cause infection. PCT and leukocyte count are indicators of the systemic inflammatory response. PCT and leukocyte count are supporting laboratory tests that can be used as biomarkers or markers of infection in COVID-19. Therefore, the purpose of this study was to determine the relationship between PCT levels and leukocyte counts in COVID-19 patients. This type of research is quantitative descriptive using a cross-sectional research design using a purposive sampling technique to obtain a sample of 41 patients and this research was conducted at Pasar Rebo Hospital. The results of the univariate statistical test and bivariate test, the results of the PCT level examination as many as 23 people (56.1%) had high PCT levels and as many as 18 people (43.9%) had normal PCT levels and 1 person (2.4%) Leukopenia, 15 people (36.6%) had a leukocyte count with normal results and as many as 25 people (61.0%) had leukocytosis. The results of data analysis showed that there was a relationship between PCT levels and leukocyte counts in COVID-19 patients of 0.468 in the range of 0.26-0.50, which means that PCT levels and leukocyte counts have a sufficient relationship